UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA MELALUI MEDIA VISUAL DI SMP NEGERI 3 CIOMAS - ASEP SUHENDAR (MGMP PAI Jawa Barat, 2022)
Educators must be able to take advantage of all forms of learning media. Educators must be creative and innovative in utilizing learning media, so that the learning process does not become monotonous. The purpose of this study was to determine the relationship between visual media and students' learning motivation in Islamic Religious Education subjects. This research uses correlation method with quantitative approach. This type of research is field research, which is to collect data or information that will be processed and analyzed to get an answer or conclusion. The results of this study based on calculations, has obtained an rxy of 0.52. By looking at the results of the r product moment value, the value of 0.52 based on the data interpretation table is between 0.40 to 0.70, so it can be concluded that the use of visual media on student learning motivation in Islamic Religious Education subjects has a significant correlation. moderate or sufficient. Then the null hypothesis (Ho) is rejected, it means that the alternative hypothesis (Ha) is accepted or in other words there is a moderate or sufficient correlation between visual media and students' learning motivation in Islamic Religious Education subjects.